A Critical Analysis of Risk Auditing: An Auditor's Approach - Susilo, Joko (Golden Ratio of Auditing Research, 2023)
analyze risk auditing, focusing on the auditor's approach, to uncover complexities and challenges inherent in contemporary auditing practices. The study synthesizes findings from a literature review, discussing implications for auditors, organizations, and future research. The multifaceted role of auditors in risk auditing involves identifying, assessing, and managing risks across financial and operational domains, ensuring organizational objectives and assets' safeguarding. Auditors must possess diverse skills, expertise, and judgment to navigate subjective risk assessment, particularly in evaluating emerging risks and complex financial instruments. Moreover, auditors must adopt a proactive approach to risk management, anticipating potential risks and providing timely recommendations. However, challenges such as the lack of standardized risk assessment practices, the rapid pace of business environment changes, and integrating emerging technologies into risk auditing persist. These challenges underscore the need for ongoing innovation and improvement in risk auditing practices. Empirical findings suggest a positive association between risk disclosures' quality and firm performance, emphasizing governance mechanisms' importance in risk management. By addressing challenges and collaborating with stakeholders, auditors can enhance risk management practices' effectiveness, safeguarding organizational objectives and assets in dynamic business environments.